(untitled) - Konecny, Pavel (Leiden, 2005)
Eurock 2005 contains the Proceedings of the International Symposium of the International Society for Rock Mechanics (ISRM), which was held 18 to 20 May 2005 in Brno, Czech Republic. This event was organized by the ISRM Czech National Group and the Institute of Geonics of the Academy of Sciences of the Czech Republic. This work focuses on the impact of human activity on the geological environment and contains over 100 papers dealing with laboratory and field research investigations in geomechanics, geoengineering and mathematical modeling. Topics covered are grouped into eight main themes: · response of the rock mass to human impact; · slope stability; · field research; · laboratory research; · stability of underground openings; · mathematical modeling; · stress measurements; and · mineral and rock disintegration. This volume offers a deeper understanding of current concerns in geomechanics
Keywords: Earth sciences